Pertumbuhan Ekonomi Masyarakat Gili Iyang Melalui Pariwisata Oksigen Perspektif: Hifdz Al-Mal - Mila Dwi Kurniawati; Subairi Syamsuri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the economic development of the Gili Iyang community influenced by oxygen tourism activities and to examine it from the perspective of Hifz al-Mal. Gili Iyang is a tourist destination in Sumenep Regency known for its high air quality, which has enabled it to develop as a health- and environment-based tourism destination. This study employed a qualitative approach with a descriptive method and was conducted through field research to obtain data directly from the research site. Data were collected through interviews, observations, and documentation involving local communities, business actors, village officials, tourists, and tourism service providers. The findings indicate that oxygen tourism has a positive impact on community economic growth, as reflected in increased local income, the development of culinary businesses, transportation services, homestays, and the creation of employment opportunities for local residents. In addition, oxygen tourism serves as a health- and environment-based tourism attraction by emphasizing air quality and environmental sustainability as its main attractions. From the perspective of Hifz al-Mal, the development of oxygen tourism reflects efforts to preserve and manage resources wisely, productively, and sustainably for the benefit of society. However, tourism development still faces challenges, including limited facilities, transportation access, and suboptimal tourism promotion. Therefore, sustainable collaboration among local communities, village governments, and other stakeholders is required to develop tourism that not only aims to increase community income but is also aligned with Islamic economic values emphasizing public welfare, justice, and sustainability.